Burnout and Associated Factors Among Medical Students in a Public University in Uganda: A Cross-Sectional Study - Kajjimu, Jonathan; Kaggwa, Mark Mohan; Bongomin, Felix (Advances in Medical Education and Practice, 2021)
Background: Burnout is a well-recognized phenomenon that may manifest with feelings of stress, fatigue, or exhaustion. It is a common and emerging problem among healthcare workers. Medical students may be at increased risk of burnout given the rigorous nature of their training. However, there is a paucity of data on the burden of burnout among medical students in Africa. Aim: This study aimed to determine the prevalence of burnout, as assessed using the Maslach Burnout Inventory – Student Survey (MBI-SS) as well as factors associated with the development of burnout among students pursuing Bachelor of Medicine and Bachelor of Surgery (MBChB) degrees at Mbarara University of Science and Technology (MUST), Uganda. Methods: A single-centre, cross-sectional, online survey was conducted among MBChB students of MUST. Burnout was assessed using the Maslach Burnout Inventory – Student Survey (MBI-SS) tool. Bivariate analysis and backward stepwise logistic regression analysis were performed to assess possible associations between variables related to participants’ demography, socioeconomic, personal, learning environment, outside school environment aspects and burnout prevalence scores. Results: A total of 145 medical students, 102 (70.3%) male, with a median (range) age of 23 (18–40) years were studied. A total of 135 students (93.1%) presented with high levels of emotional exhaustion, 90 (62.1%) students had low levels of professional efficacy scores and 141 (97.2%) of the medical students had high levels of cynicism. Overall, 79 (54.5%) students had burnout, as defined by the MBI-SS tool. Choosing MBChB willingly appears to be an independent predictor of burnout (Adjusted odds ratio: 7.2; 95% CI: 1.4–36.9; p=0.018). Conclusion: More than one-half of medical students questioned at MUST do experience a degree of burnout. Preventative and interventional measures should be considered in the development of the medical curriculum
Keywords: Medical students; Burnout; Maslach Burnout Inventory; Mental health; Wellbeing; Uganda